Lack of intracranial atherosclerosis in various atherosclerotic mouse models - Diewertje I Bink; Katja Ritz; Claire Mackaaij; Olga Stam; Sanny Scheffer; Mark R Mizee; Hanneke J Ploegmakers; Bert J van het Hof; Onno J de Boer; Judith C Sluimer; Guido R Y De Meyer; Louise van der Weerd; et al. (Vascular Biology)
Although mice are used extensively to study atherosclerosis of different vascular beds, limited data are published on the occurrence of intracranial atherosclerosis. Since intracranial atherosclerosis is a common cause of stroke and is associated with dementia, a relevant animal model is needed to study these diseases. We examined the presence of intracranial atherosclerosis in different atherogenic mouse strains and studied differences in vessel wall characteristics in mouse and human tissue in search of possible explanations for the differing atherosclerotic susceptibility between extracranial and intracranial vessels. The presence of atherosclerotic plaques was systematically examined from the distal common carotids to the circle of Willis in three atherogenic mouse models. Extra- and intracranial vessel characteristics were studied by immunohistochemistry. All three strains developed atherosclerotic lesions in the common carotids, while no lesions were found intracranially. This coincided with altered vessel morphology. Compared to extracranial sections, intracranially the number of elastic layers decreased, tight junction markers increased, and antioxidant enzyme heme oxygenase (HO)-1 increased. Higher HO-1 expression was also shown in human intracranial arteries. Human brain endothelial cell stimulation with oxidized LDL induced endogenous protective antioxidant HO-1 levels through NRF2 translocation. Intracranial atherosclerosis was absent in three atherogenic mouse models. Intracranial vessel segments showed an increased presence of junction markers in mice and increased HO-1 in both mice and human tissue. We suggest that differences in brain vessel structure and induced antioxidant levels in the brain endothelium found in mouse and human tissue may contribute to the decreased atherosclerosis susceptibility of intracranial arteries.